Stainless steel in municipal waste water treatment plants - Tuthill, Arthur H.; Lamb, S. (Technical series (Nickel Development Institute (Canada)) ;, 1995)
This article reviews the suitability and performance of the several grades of stainless steel that have been used or consider for waste water treatment plant and identify guidelines that will assist the user to obtain the best result from the stainless steel selected for these plants.